Characterization and efficacy of chitosan membranes in the treatment of skin ulcers. Issue 1 (2nd January 2019) - López-Cervantes, Jaime; Escárcega-Galaz, Ana A.; Sánchez-Machado, Dalia I.; De La Cruz-Mercado, José L.; Pérez-Gómez, Luis E.; Ornelas-Aguirre, José M.
ABSTRACT: Chronic wounds aggravate the patient's indisposition by causing mobility, economic and social problems. Chitosan is a natural polymer that is considered a potent healing agent for skin lesions and has been used previously to manufacture dressings for wounds. The aim of this work was to evaluate the curative effect of chitosan membranes on cutaneous ulcers. The chitosan was characterized by measuring the degree of deacetylation and FTIR. The membranes were obtained by a solvent evaporation technique. Four patients with cutaneous ulcers were recruited to evaluate the effectiveness of the topical membranes. At the beginning of the in vivo assay, patients presented with infected wounds. By the end of treatment, the infection subsided, the granulation process was promoted and complete skin coverage was observed in most patients. The use of chitosan as a treatment for the healing of skin ulcers is considered highly promising for its medicinal properties, as well as for its affordability compared to traditional treatments. Graphical abstract: